Fruit fly as a biological model for detecting the effects and toxicity of environmental pollutants on living organisms in the city of Benghazi - حنان محمود محمد اجبيدة; انتصار احمد المصلي; حنان خليفة بوخمادة; سعاد صالح ادم (African Journal of Advanced Pure and Applied Sciences, 2026)
The risk of environmental pollution is increasing year after year. To assess the impact and toxicity of pollution, the fruit fly (Drosophila melanogaster) was used as a biological tool for this purpose. Accordingly, this study was conducted in several geographical locations within the city of Benghazi with the aim of monitoring and characterizing morphological mutations in the fly to detect the presence of environmental pollutants in the area.Random samples were collected from several regions during two consecutive seasons, namely the spring season 2024/2025 and the autumn season 2025/2026. The results of the morphological analysis showed the occurrence of a mutation related to wing deformity during the spring season in the areas of Sidi Khalifa, Al-Salam district, and Al-Majouri. In contrast, the same mutation was observed during the autumn season in the regions of Al-Halis, Qanfouda, and Al-Fuwayhat, along with a noticeable enlargement of the eyes in some samples collected from the Buatni area, indicating a possible variation in mutation patterns depending on environmental differences between locations.It is noteworthy that all individuals carrying the recorded mutations were females, except in the Al-Majouri area, while in the autumn season males were recorded in the areas of Al-Halis and Al-Fuwayhat. Statistical analysis showed that the percentages of affected males, females, and overall cases were (13.1 - 17.0 - 16.1)%, respectively, with an increase in infection cases in the second season, and females had higher rates in both seasons.The Chi-square results showed statistical significance in the regions and in the mutated cases for males, females, and overall, estimated at 27.1 - 45.8 - 120 - 165.4, respectively, at P < 0.05. The highest infection rate was observed in western Benghazi, and the infection ratio for males was one for every four females. This supports the need for further studies to understand and clarify the relationship between sex and mutation occurrence.